The Responsibility Principles in The Framework of Good Corporate Governance of The Social Welfare Institution in The Special Region of Yogyakarta - Sugiyanto, Sugiyanto; Tjahjono, Heru Kurnianto; Hartono, Arief; Khuluq, Lathiful (FEB - Universitas Lampung, 2019)
This research of responsibility in the framework of good corporate governance aims to know the responsibility principles in the framework of good corporate governance and governance model of social welfare institution (LKS) in the Special Region of Yogyakarta (DIY). This type of study is a case study. The type of research conducted is descriptive qualitative, that is the researchers give an idea about the responsibility principles in the framework of good corporate governance of social welfare institution in DIY. The result of the research shows that there are fie responsibility principles which happened to social welfare institution in DIY and there are fie governance models of social welfare institution in DIY. Although the study was conducted for 8 years, this study still has weaknesses. It is advisable for further research to analyze thecorrelation between indicators of good corporate governance. The implications of the research are used as a reflection for policymakers, managers of LKS and donors.